La cultura de los "trabajadores" autónomos - Cayuela Sánchez, Salvador; Schriewer, Klaus (Sociología del Trabajo, 2017)
El artículo presenta el concepto teórico del modo de vida de autónomo, elaborado por investigadores escandinavos que de manera innovadora y repensando aportaciones del debate marxista diseñan nociones básicas de la cultura del “trabajador” autónomo. En un primer capítulo revisa el debate sobre autónomos en la agricultura con el fin de averiguar problemas conceptuales en la forma de concebir este grupo social. Partiendo de estos resultados explica los rasgos más importantes de la cultura de los autónomos: el trabajo autodeterminado, los conceptos de responsabilidad y libertad, el papel de la familia y las estrategias de los autónomos.The culture of the self-employed (Abstract)The article presents the theoretical concept of the Life-Mode of the Self-Employed, worked out by Scandinavian investigators who design the basic principles of the culture of the independent “worker” in an innovative manner and by reconsidering the content of the Marxist argument.The first chapter reviews the debate about self-employment in the agricultural sector in order to ascertain conceptual problems to understand this social group. Using these results, the second chapter explains the most important traits of the culture of self-employed people: the self-determined work, the concepts of responsibility and liberty, the family component and the strategies of the self-employed.
Keywords: Life-Mode Theory; simple commodity production; work; responsibility; freedom.